Nanohybrid double network hydrogel based on nanoenzyme complex and its preparation method and application

By modifying the nanoenzyme on the surface of oxygen-carrying microspheres and hybridizing with the dual network hydrogel, a multifunctional diabetic wound dressing with catalytic, oxygen-carrying, antibacterial and other diabetic wound dressing was developed, which solved the problem of single function and short-acting effect of existing dressings, significantly improving the healing effect of diabetic wounds.

CN116019973BActive Publication Date: 2025-03-07SOUTHEAST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310067589.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-18
Publication Date
2025-03-07
Estimated Expiration
2043-01-18

AI Technical Summary

Technical Problem

The existing diabetic wound dressings have a single function and short time-consuming effect, which cannot meet the diverse needs of different wound healing stages, resulting in unsatisfactory treatment results.

Method used

A nanohybrid double network hydrogel based on nanoenzyme complex was developed. By modifying the nanoenzyme on the surface of oxygen-carrying microspheres and dynamically hybridizing with the double network hydrogel, it forms a dressing with catalytic, oxygen-carrying, antibacterial and other functions.

Benefits of technology

This hydrogel can act on the wound surface for a long time, lower blood sugar levels, regulate pH microenvironment, remove bacterial infections, reshape the redox microenvironment, significantly improve the healing effect of diabetic wounds, and achieve multifunctional and long-term treatment for full-stage healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116019973B_ABST
    Figure CN116019973B_ABST
Patent Text Reader

Abstract

The present invention discloses a nano-hybrid double network hydrogel based on a nano-enzyme complex, and a preparation method and application thereof. The nano-hybrid double network hydrogel prepared by the present invention combines the catalytic function of nano-enzymes with the mechanical properties of hydrogels simulating ECM, and has functional characteristics such as oxygen supply, enzyme catalysis, antibacterial, self-healing, injectable, tissue adhesion, and remodeling of redox microenvironment. The nano-hybrid double network hydrogel of the present invention accelerates the healing of diabetic wounds by lowering the blood sugar level at the wound, regulating the pH microenvironment of the wound, clearing bacterial infection, remodeling the redox microenvironment of the wound, and conforming to the tissue to form a physical barrier, realizing a multifunctional long-acting hydrogel dressing that integrates a variety of characteristic functions suitable for diabetic wounds and covers all stages of wound healing, providing long-acting and diversified therapeutic effects for all stages of healing, and significantly improving the therapeutic effect of diabetic wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer hydrogels, and in particular relates to a nano-hybrid double network hydrogel based on a nano-enzyme complex, a preparation method thereof, and an application thereof in the treatment of diabetic wounds. Background Art

[0002] At present, many polymer hydrogel dressings have been studied, and some of them have been approved for clinical wound care and treatment. Diabetic foot (DFU) is the most common complication in patients with diabetes and hyperglycemia. It has high morbidity, mortality and recurrence rates and is the main cause of non-traumatic amputation worldwide. Wound healing is a complex process, which is usually divided into four stages: hemostasis, inflammation, proliferation and remodeling. However, the four stages cannot proceed smoothly in diabetic wounds, which are characterized by long-term low-grade inflammation, which will slow down or hinder wound healing. At the cellular level, high glucose concentrations inhibit the proliferation of fibroblasts, keratinocytes and endothelial cells, hinder angiogenesis and re-epithelialization. Hypoxia is one of the most important prognostic determinants of wound repair. The three processes of inflammation, proliferation and matrix remodeling are significantly dependent on the nutrient and oxygen supply of blood vessels and cells involved in the healing process. Keratinocyte proliferation and migration and endothelial tubule formation require angiogenesis. New blood vessels can alleviate the lack of nutrients and oxygen, which determines the healing effect of diabetic wounds. In addition, the failure of spontaneous wound healing will greatly increase the risk of bacterial infection. The most dangerous pathogens in DFU include Staphylococcus aureus. The above-mentioned aerobic pathogens rapidly deteriorate the health status of diabetic patients, making them difficult to cure and endangering their quality of life. Therefore, how to reduce the blood glucose concentration on the wound surface, improve the hypoxic environment of the wound, and eliminate bacterial infection is the key to improving the healing of diabetes. Clinical treatments for diabetic wounds include blood glucose control, surgical debridement, transplantation, and wound dressings. However, there is still no sustained, effective, and widely applicable therapy to treat chronic and difficult-to-heal DFUs, so it is crucial to further develop new methods for the treatment of diabetic wounds with long-term treatment and diverse functions.

[0003] In recent decades, many methods targeting various steps of wound healing have been studied for the treatment of chronic wounds such as diabetic foot. These methods include different types of dressings, delivery of cytokines and growth factors, cell therapy, and application of electrical or mechanical stimulation. Among all these technologies, the use of artificial structures as temporary substances to support the wound healing process is considered to be the most effective strategy. In view of this, different categories of biomaterial wound dressings have recently been developed to mimic the skin microenvironment. Among these biomaterials, hydrogels with biomimetic structures and physical properties have been widely used in wound healing applications. Their high biocompatibility and excellent drug controlled release ability make hydrogels an ideal biomaterial. However, traditional hydrogels have a single function and only function in a single stage of wound healing. They have a single function and limited effect. They cannot meet the diverse needs of different stages of wound healing and have unsatisfactory therapeutic effects. Therefore, there is a great need for hydrogels that can match the needs of different wound healing stages, play different roles in different stages, and provide therapeutic effects covering all stages.

[0004] Nanomaterials with excellent enzyme-like catalytic activity have been defined as nanozymes. Artificial nanozymes have attracted widespread interest due to their wide advantages over natural enzymes, such as environmental friendliness, low cost, easy production, adjustable catalytic activity, and recyclability. Pt nanoparticles have been shown to have the ability to catalyze the conversion of H2O2 to highly toxic ·OH under weakly acidic pH conditions, namely peroxidase-like (POD) activity. Pt nanoparticles can decompose H2O2 into non-toxic water and oxygen under neutral pH conditions, showing catalase-like (CAT) activity. Pt nanoparticles can mimic glucose oxidase (GOX) to catalyze the conversion of glucose into gluconic acid and H2O2. Pt nanoparticles also have superoxide dismutase (SOD)-like activity, which can rapidly convert harmful O2·- into H2O2 and O2, acting as O2·- scavengers. Nanoparticles with multiple enzyme activities at the same time are related to the catalytic conditions. Nanozymes exert different enzyme activities under different pH conditions. Pt nanoparticles can play different roles in different stages of diabetic foot wound healing. GOX-like enzyme activity can reduce the glucose content on the wound surface and adjust the high-sugar environment of the wound. At the same time, POD-like enzyme activity can produce reactive oxygen species to fight bacteria, and superoxide dismutase-like and catalase-like activities can remove excess reactive oxygen species in the later stage and reshape the wound redox microenvironment. The pH-dependent multi-type enzyme activity of nanozymes can meet the healing needs of wounds at different stages, and can play different functions according to the changes in the wound microenvironment, creatively meeting the healing needs of wounds at all stages. However, the retention problem of nanomaterials in the wound limits its role. Nanozymes are easily metabolized due to their nanosize, making it difficult to remain in the wound for a long time and having a short action time. Hybridizing nanozymes to hydrogels so that they can dynamically combine with the hydrogel network can effectively solve the retention problem, allowing nanozymes to act on the wound surface for a long time while meeting the wet healing environment required by the wound. Summary of the invention

[0005] Purpose of the invention: In view of the problems of the existing diabetic wound dressings having single functions and short duration of action, one of the purposes of the present invention is to provide a nanohybrid double network hydrogel based on a nanozyme complex with good catalytic and oxygen-carrying properties and biocompatibility.

[0006] The second object of the present invention is to provide a method for preparing a nanohybrid double network hydrogel based on a nanozyme complex.

[0007] The third object of the present invention is to provide the application of nanohybrid double network hydrogel based on nanoenzyme complex in diabetic wound healing.

[0008] Technical solution: In order to solve the above technical problems, the present invention provides a nanohybrid double network hydrogel based on a nanozyme complex, wherein the nanohybrid double network hydrogel is obtained by dynamic non-covalent hybridization of a double network hydrogel and a nanozyme complex, and the nanozyme complex has oxygen-carrying microspheres as the core and is surface-modified with nanozymes.

[0009] The oxygen-carrying microspheres are high molecular copolymer nano-microspheres loaded with oxygen carriers, and the particle size of the high molecular copolymer nano-microspheres loaded with oxygen carriers is 120-200 nm.

[0010] The nanozyme is an ultra-small nanozyme with a diameter of 2 to 5 nm, and the hydrodynamic size of the nanozyme complex is 150 to 300 nm.

[0011] Since the nanozyme complex of the present invention is to modify the nanozyme on the surface of the polymer nanosphere, the stability, particle size, and surface groups of the polymer nanosphere need to be considered to achieve a good coating effect. The stability, particle size, and surface groups of the polymer nanosphere depend on the raw material ratio and preparation method used.

[0012] The present invention also includes a method for preparing the nanohybrid double network hydrogel based on the nanoenzyme complex, comprising the following steps:

[0013] (1) Using polyethylene glycol as a coating agent, adding a reducing agent and chloroplatinic acid, and stirring to obtain an ultrasmall nanozyme;

[0014] (2) Using high molecular copolymer as carrier and polyvinyl alcohol as emulsifier, nanoparticles loaded with oxygen carrier are prepared by solvent evaporation method;

[0015] (3) mixing the ultrasmall nanozyme with an aqueous solution of nanospheres loaded with an oxygen carrier, adding dicyclohexylcarbodiimide, and placing the mixture on a constant temperature shaker for reaction, wherein the ultrasmall nanozyme is coupled to the surface of the nanospheres through an amide bond to obtain a nanozyme complex;

[0016] (4) A high molecular weight polymer, an initiator, a cross-linking agent, and a nanoenzyme complex are mixed to obtain a reaction solution, the reaction solution is injected into a mold, and a nano-hybrid double network hydrogel is prepared through a photo-initiated free radical polymerization reaction.

[0017] Wherein, the molecular weight of the polyethylene glycol in step (1) is 2000-5000. Preferably, the molecular weight of the polyethylene glycol used in step (1) is 2000, 3500 or 5000.

[0018] Wherein, the final concentration of polyethylene glycol is 5-30 mg / mL, the final concentration of the reducing agent is 1-3 mg / mL, and the final concentration of chloroplatinic acid is 1-2 mg / mL;

[0019] The reducing agent in step (1) includes but is not limited to one or more of sodium borohydride, sodium citrate or L-ascorbic acid; in a specific embodiment of the present invention, the reducing agent is preferably sodium borohydride.

[0020] Wherein, the stirring time of step (1) is 30 min to 60 min; and the diameter of the ultrasmall nanozyme is 2 to 5 nm.

[0021] The specific steps of step (2) are as follows: dissolving the oxygen carrier and the high molecular copolymer in chloroform, adding the mixture to a polyvinyl alcohol aqueous solution, ice bathing and ultrasonically crushing the mixture, and mechanically stirring the mixture at a constant temperature to volatilize the chloroform.

[0022] The polymer copolymer in step (2) includes but is not limited to polylactic acid-glycolic acid or polylactic acid with a carboxyl group at the end; the biocompatible polymer copolymer has good hydrophilicity and can be used to encapsulate hydrophobic drugs. At the same time, it has abundant functional groups on the surface and is easy to modify to achieve specific modification purposes.

[0023] In a specific implementation case of the present invention, the polymer copolymer is preferably polylactic acid-glycolic acid.

[0024] Wherein, the final concentration of the polymer copolymer in step (2) is 3 to 6 mg / mL;

[0025] The oxygen carrier suitable for the present invention includes, but is not limited to, one or a combination of perfluorooctane bromide, perfluoroheptane bromide, and perfluorohexane bromide.

[0026] The final volume percentage of the oxygen carrier in chloroform in step (2) is 5% to 20%; the ultrasonic crushing time is 2 to 5s, the ultrasonic interval time is 2 to 5s, the power is 100 to 250W, and the number of ultrasonic times is 60 to 100; the mechanical stirring time is 2 to 5h, the stirring temperature is 20 to 25°C, and the stirring speed is 300 to 450rpm.

[0027] In a specific implementation case of the present invention, the oxygen carrier is preferably perfluorooctane bromide.

[0028] Wherein, the volume ratio of the ultrasmall nanoenzyme to the aqueous solution of nano-microspheres loaded with oxygen carrier in step (3) is 1:1-1.5:1; the temperature of the constant temperature shaker is 30-40°C, the rotation speed is 100-250r / min, and the coupling time is 30-60min.

[0029] Preferably, step (3) specifically comprises: mixing the ultrasmall platinum nanozyme with an aqueous solution of nanospheres loaded with an oxygen carrier in a volume ratio of 1:1 or 1.5:1, adding dicyclohexylcarbodiimide (DCC), placing the mixture on a constant temperature shaker to react for 30 to 60 minutes, and finally centrifuging to remove free polyethylene glycol, platinum nanozyme and polyvinyl alcohol to obtain a platinum nanozyme complex (PFOB@PLGA@Pt).

[0030] Wherein, the high molecular polymer in step (4) includes high molecular A and high molecular B;

[0031] Wherein, the polymer A includes but is not limited to one or more of methacrylated gelatin, poly(ethylene glycol) diacrylate or methacrylated chitosan. In a specific embodiment of the present invention, the polymer A is preferably methacrylated gelatin.

[0032] Wherein, the polymer B includes but is not limited to one or more of oxidized dextran, oxidized hyaluronic acid, and oxidized sodium alginate; in a specific implementation case of the present invention, the polymer B is preferably oxidized dextran.

[0033] Among them, the mass percentage of the polymer A is 5% to 25%, and the mass percentage of the polymer B is 5% to 25%; the cross-linking agent is N, N-methylenebisacrylamide, and the photoinitiator is phenyl (2,4,6-trimethylbenzoyl) lithium phosphate; the free radical polymerization reaction is a blue light-initiated free radical polymerization reaction, the blue light wavelength is 405nm, the power is 40 to 50w, the light initiation distance is 1 to 3cm, and the illumination time is 10 to 20s.

[0034] The present invention also includes the use of the nano-hybrid double network hydrogel based on the nano-enzyme complex in the preparation of diabetic wound healing adjuvants.

[0035] The nano-hybridized double-network hydrogel based on the nano-enzyme complex of the present invention has a high molecular polymer nano-microsphere loaded with an oxygen carrier as the core, and an ultra-small nano-enzyme is modified on the surface. The amine groups on the surface of the nano-complex are hybridized to the double-network gel. The gel maintains the catalytic and oxygen-carrying properties of the nano-enzyme complex and has good biocompatibility.

[0036] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the nano-hybrid double network hydrogel prepared by the present invention combines the catalytic function of nanoenzymes with the mechanical properties of hydrogels simulating ECM, and has functional characteristics such as oxygen supply, enzyme catalysis, antibacterial, self-healing, injectable, tissue adhesion, and remodeling of the redox microenvironment. The nano-hybrid double network hydrogel of the present invention accelerates the healing of diabetic wounds by reducing the blood sugar level at the wound, regulating the pH microenvironment of the wound, clearing bacterial infection, remodeling the redox microenvironment of the wound, and forming a physical barrier by conforming to the tissue, realizing a multifunctional long-acting hydrogel dressing that integrates multiple characteristic functions suitable for diabetic wounds and covers the entire stage of wound healing, providing long-term and diversified therapeutic effects for all-stage healing, and significantly improving the therapeutic effect of diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Transmission electron microscopy images of Pt NPs, PFOB@PLGA, and PFOB@PLGA@Pt nanospheres.

[0038] Figure 2 This is the particle size distribution diagram of PFOB@PLGA and PFOB@PLGA@Pt nanospheres.

[0039] Figure 3 This is the scanning electron microscopy image of PFOB@PLGA@Pt / GelMA / ODex.

[0040] Figure 4 Diagram of PFOB@PLGA@Pt / GelMA / ODex tissue adhesion, injectability, self-healing, and enzyme catalysis.

[0041] Figure 5 The results of PFOB@PLGA@Pt / GelMA / ODex against Staphylococcus aureus in vitro.

[0042] Figure 6 Biosafety study of PFOB@PLGA@Pt / GelMA / ODex (scale: 50 μm).

[0043] Figure 7 The therapeutic effect of PFOB@PLGA@Pt / GelMA / ODex on diabetic wounds.

[0044] Figure 8 It is a schematic diagram of the formation process of the nano-hybrid double network hydrogel of the present invention and the wound repair process. DETAILED DESCRIPTION

[0045] In order to better understand the present invention, the present invention is further illustrated by the following examples, but the content of the present invention is not limited to the following examples.

[0046] Example 1 Preparation of Pt NPs Ultrasmall Nanozymes

[0047] 1 ml of chloroplatinic acid (10 mg / mL) and 10 mg of polyethylene glycol (SH-PEG-NH2, Mn (number average molecular weight) is 2000) were dissolved in 10 mL of pure water, 1 mL of sodium borohydride aqueous solution (10 mg / mL) was added in an ice bath, and mechanically stirred at 500 rpm for 30 min to obtain ultrasmall platinum nanozymes (Pt NPs), wherein the concentration of platinum in the ultrasmall platinum nanozymes (Pt NPs) was 270 mg / L.

[0048] Example 2 Preparation of PFOB@PLGA Nanospheres Loaded with Oxygen Carrier

[0049] 50mg polylactic acid-glycolic acid (PLGA, provided by Shandong Academy of Pharmaceutical Sciences, wherein lactic acid:glycolic acid is 50:50, viscosity 0.1dL / g (CHCl3 / 25℃)) and 150μL perfluorooctyl bromide (PFOB) were ultrasonically dissolved in 3mL of chloroform, and added to 10mL of 2% polyvinyl alcohol (PVA, 88% hydrolyzed, average MW20000-30000) aqueous solution, ice bath and ultrasonically broken (time is 2s, ultrasonic interval time is 3s, power is 120W, ultrasonic times is 60). Constant temperature is 25℃, mechanical stirring is 450rpm, and 2h is used to volatilize the organic reagent to obtain polylactic acid-glycolic acid nanospheres (PFOB@PLGA) aqueous solution.

[0050] Example 3 Preparation of PFOB@PLGA@Pt nanozyme complex

[0051] 5 mL of ultrasmall platinum nanozyme (Pt NPs) was mixed with 5 mL of polylactic acid-glycolic acid nanosphere aqueous solution (PFOB@PLGA), 2 mL of dicyclohexylcarbodiimide (10 mg / mL) was added, and the mixture was placed on a constant temperature shaker at 37°C for 60 min. Finally, the mixture was centrifuged (3 times, at a speed of 4500 rpm for 10 min) to remove free polyethylene glycol, platinum nanozyme and polyvinyl alcohol. After centrifugation, ultrapure water was added to re-dissolve the mixture to 5 mL to obtain a platinum nanozyme complex (PFOB@PLGA@Pt) (wherein the platinum concentration was 270 mg / L).

[0052] Example 4 Preparation of PFOB@PLGA@Pt / GelMA / ODex Nanohybrid Double Network Hydrogel

[0053] 0.1g of methacrylic anhydride gelatin (Site Biotechnology Co., Ltd., item number: R201C2) was dissolved in 1mL of pure water, 0.01g of initiator phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt, 0.005g of cross-linking agent N, N-methylenebisacrylamide were added, mixed in a constant temperature water bath, and then 0.1g of oxidized dextran (Xi'an Ruixi Biotechnology Co., Ltd., MW100,000) and 150μL of platinum nanozyme complex (PFOB@PLGA@Pt, where the platinum concentration was 270mg / L) were added, and mixed evenly to obtain a reaction solution. The reaction solution was injected into the mold, 405nm blue light, power of 40w, light initiation distance of 1cm, illumination time of 10s, to initiate free radical polymerization reaction, and three nanohybrid double network hydrogels (PFOB@PLGA@Pt / GelMA / ODex) based on nanozyme complexes were prepared (platinum concentration was 35μg / mL).

[0054] Example 5 Characterization of Pt NPs, PFOB@PLGA, and PFOB@PLGA@Pt nanozyme complexes

[0055] A small amount of Pt NPs, PFOB@PLGA and PFOB@PLGA@Pt nanozyme complex prepared in the above steps was coated on a copper grid, and the morphology and particle size of the nanoparticles were observed using a transmission electron microscope. Figure 1 As shown, Pt NPs TEM results show that Pt NPs have good dispersibility and stability, with an average particle size of 2-5 nm. PFOB@PLGA nanospheres are spherical, with uniform particle size distribution (100-300 nm), no agglomeration, and good stability; black Pt nanoparticle clusters can be clearly seen in the PFOB@PLGA@Pt nanozyme complex image, and EDS energy spectrum results show that it mainly contains C, N, O, F, and Pt elements;

[0056] like Figure 2 As shown in the figure, the hydrodynamic size of PFOB@PLGA and PFOB@PLGA@Pt nanospheres was measured by Malvern particle size analyzer. The average particle size of PFOB@PLGA nanospheres was about 100nm, and the average size of PFOB@PLGA@Pt nanospheres was about 250nm, which proved that the particle size of the microspheres would increase after the modification of platinum nanozymes.

[0057] Example 6 PFOB@PLGA@Pt / GelMA / ODex tissue adhesion, injectability, self-healing, enzyme catalysis, oxygen carrying function

[0058] Tissue adhesion performance: Take two pieces of pig skin tissue (3cm*3cm, remove hair and wash) (purchased from Jinxianghe Farmers' Market in Nanjing), add 0.02g methacrylate anhydride gelatin (GelMA, Si Te Yi Biotechnology Co., Ltd., item number: R201C2), 0.02g oxidized dextran (ODex, Xi'an Ruixi Biotechnology Co., Ltd., MW100,000), add 0.002g initiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 0.001g cross-linking agent N,N-methylenebisacrylamide, dissolve in 0.2mL pure water, and then add 30μL of PFOB@PLGA@Pt nanozyme complex prepared in Example 3. After mixing, inject it into the gap between the skin and observe the adhesion of the gel to the tissue after irradiation with a 405nm light source for 20s. Self-healing performance: The gel was stained with Coomassie Brilliant Blue and o-phenanthroline, respectively, and the stained gel was placed in a wet box for 3h and then the self-healing was observed. Oxygen carrying capacity test: PFOB@PLGA@Pt / GelMA / ODex hydrogel was synthesized in situ in a well plate, 2 mL of oxygen-free water was added to the well plate, and the needle-type dissolved oxygen probe was used to measure the changes in oxygen content inside the gel. Peroxidase-like activity: 1 mL of HAc-NaAc (pH 4.4, 1 M) buffer, 100 μL of H2O2 (10 M), and 50 μL of TMB (10 mg / mL) were added to 400 μL of PFOB@PLGA@Pt / GelMA / ODex hydrogel, and the color change of the hydrogel was recorded. Catalase-like activity: 200 μL of H2O2 (10 M) was added to 400 μL of PFOB@PLGA@Pt / GelMA / ODex hydrogel, and the changes in the hydrogel were recorded.

[0059] like Figure 3 , 4 As shown, the nanohybrid double network hydrogel has a good mesh structure and has tissue adhesion, self-healing and injectable properties. Due to the presence of PFOB oxygen carrier, the rate of oxygen decline in PFOB@PLGA@Pt / GelMA / Odex hydrogel is slower. The obvious blue color of the hydrogel in the peroxidase activity test indicates that a large number of bubbles are quickly generated in the catalase activity test, and the decrease in pH in the glucose oxidase test indicates the excellent enzyme catalytic performance of the hydrogel.

[0060] Example 7 PFOB@PLGA@Pt / GelMA / ODex hydrogel against Staphylococcus aureus in vitro

[0061] According to the method of Example 4, PFOB@PLGA@Pt / GelMA / ODex hydrogels with different platinum concentrations (0, 13, 35 μg / mL) were synthesized in a 12-well plate by adding different volumes (0, 10, 30 μL) of platinum nanozyme complex (PFOB@PLGA@Pt, wherein the platinum concentration was 270 mg / L), PBS (1 M, pH 6.0, containing 20 mM glucose) was added as a carbon source, and 10 μl of Staphylococcus aureus bacterial suspension (10 6 CFU mL -1 ), incubate at 37°C for 4 h. After 24 h, resuspend the bacterial solution, take 100 μL and spread it on LB solid plate culture medium, and culture at 37°C for 24 h.

[0062] like Figure 5 As shown, PFOB@PLGA@Pt / GelMA / ODex hydrogel has excellent antibacterial properties against Staphylococcus aureus.

[0063] Example 8 PFOB@PLGA@Pt / GelMA / ODex Biosafety Study

[0064] PFOB@PLGA@Pt / GelMA / ODex hydrogels (Pt concentration: 35 μg / mL) were pre-synthesized in 12-well plates, sterilized overnight under UV light, and supplemented with 10% fetal bovine serum (Gibco), dulbecco's modified eagle medium (DMEM) (Gibco), 1.0×10 5 UL -1 Penicillin (Hyclone) and 100 mg / L streptomycin (Hyclone) were used as complete growth medium. HUVEC, L929, and RAW264.7 cells were cultured at 5×10 4 The cells were inoculated on the gel at a density of 100 / mL. After 72 hours of co-culture, the cell compatibility was evaluated using the Calcein AM·PI (Cell Viability / Cytotoxicity Detec) kit.

[0065] like Figure 6 As shown, PFOB@PLGA@Pt / GelMA / ODex hydrogel has good biosafety and cell adhesion.

[0066] Example 9 Effect of PFOB@PLGA@Pt / GelMA / ODex on the treatment of diabetic wounds

[0067] After the wound modeling of diabetic rats was successfully established, the wounds were treated with control (PBS buffer (1M, pH 7.4)), GelMA / ODex hydrogel (0.02g methacrylic anhydride gelatin (GelMA, Steyi Biotechnology Co., Ltd., catalog number: R201C2), 0.02g oxidized dextran (ODex, Xi'an Ruixi Biotechnology Co., Ltd., MW100,000), 0.002g initiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 0.001g cross-linking agent N,N-methylenebisacrylamide, dissolved in 0.2mL pure water, irradiated with a 405nm light source for 20s to obtain GelMA / ODex hydrogel), and the PFOB@PLGA@Pt / GelMA / ODex hydrogel synthesized in Example 4. Wound photos were taken on the 3rd, 6th, and 9th days, and the wounds of the mice were excised on the 3rd, 6th, and 9th days, and then placed in sterile saline (1mL). Bacterial samples were then collected from the wounds after incubation at 37°C for 24 h.

[0068] like Figure 7 As shown, the PFOB@PLGA@Pt / GelMA / ODex group showed a faster wound healing speed, and the number of wound bacteria was significantly lower than that of the control group at six and nine days.

Claims

1. A nanohybrid double network hydrogel based on a nanozyme complex, characterized in that: The nano hybrid double network hydrogel is obtained by hybridizing the double network hydrogel and the nano enzyme complex through dynamic non-covalent bonds. The nano enzyme complex has oxygen-carrying microspheres as the core and the surface is modified with nano enzymes. The oxygen-carrying microspheres are high molecular copolymer nano microspheres loaded with oxygen carriers. The preparation method of the nano hybrid double network hydrogel based on the nano enzyme complex comprises the following steps: (1) Using polyethylene glycol as a coating agent, adding a reducing agent and chloroplatinic acid, and stirring to obtain an ultrasmall nanozyme; (2) Using high molecular copolymer as carrier and polyvinyl alcohol as emulsifier, the nanoparticles loaded with oxygen carrier are prepared by solvent evaporation method; (3) mixing the ultrasmall nanozyme with an aqueous solution of nanospheres loaded with oxygen carriers, adding dicyclohexylcarbodiimide, and placing the mixture on a constant temperature shaker for reaction, wherein the ultrasmall nanozyme is coupled to the surface of the nanospheres through an amide bond, thereby obtaining a nanozyme complex; (4) A polymer, a photoinitiator, a cross-linking agent, and a nanozyme complex are mixed to obtain a reaction solution, the reaction solution is injected into a mold, and a nano-hybrid double network hydrogel is obtained through a photo-initiated free radical polymerization reaction; the oxygen-carrying microspheres are polymer copolymer nano-microspheres loaded with oxygen carriers, the particle size of the polymer copolymer nano-microspheres loaded with oxygen carriers is 120-200 nm, the nanozyme is an ultra-small nanozyme, the diameter of the ultra-small nanozyme is 2-5 nm, and the hydrodynamic size of the nanozyme complex is 150-300 nm.

2. The method for preparing the nanohybrid double network hydrogel based on the nanozyme complex according to claim 1, characterized in that: The following steps are involved: (1) Using polyethylene glycol as a coating agent, adding a reducing agent and chloroplatinic acid, and stirring to obtain an ultrasmall nanozyme; (2) Using high molecular copolymer as carrier and polyvinyl alcohol as emulsifier, the nanoparticles loaded with oxygen carrier are prepared by solvent evaporation method; (3) mixing the ultrasmall nanozyme with an aqueous solution of nanospheres loaded with oxygen carriers, adding dicyclohexylcarbodiimide, and placing the mixture on a constant temperature shaker for reaction, wherein the ultrasmall nanozyme is coupled to the surface of the nanospheres through an amide bond, thereby obtaining a nanozyme complex; (4) mixing a high molecular weight polymer, a photoinitiator, a crosslinking agent, and a nanoenzyme complex to obtain a reaction solution, injecting the reaction solution into a mold, and obtaining a nanohybrid double network hydrogel through a photoinitiated free radical polymerization reaction; The molecular weight of the polyethylene glycol in step (1) is 2000-5000, the final concentration of the polyethylene glycol is 5-30 mg / mL, the final concentration of the reducing agent is 1-3 mg / mL, and the final concentration of chloroplatinic acid is 1-2 mg / mL; the reducing agent is sodium borohydride, sodium citrate or L-ascorbic acid; the stirring time is 30 min-60 min; the diameter of the ultra-small nanozyme is 2-5 nm; the specific steps of step (2) are: dissolving the oxygen carrier and the high molecular copolymer in chloroform, adding them to the polyvinyl alcohol aqueous solution, ice bathing and ultrasonic crushing, constant temperature mechanical stirring to volatilize the chloroform; the high molecular copolymer in step (2) includes polylactic acid-glycolic acid or polylactic acid with a carboxyl group at the end; the final concentration of the high molecular copolymer is 3-6 mg / mL, the oxygen carrier is perfluorooctane bromide, perfluoroheptane bromide or perfluorohexane bromide; the final volume percentage of the oxygen carrier in chloroform is 5%~20%; the ultrasonic crushing time is 2~5 s, the ultrasonic interval time is 2~5 s, the power is 100~250 W, and the number of ultrasonic times is 60~100; the mechanical stirring time is 2~5 h, the stirring temperature is 20~25°C, the stirring speed is 300~450 rpm, the volume ratio of the ultrasmall nanoenzyme in step (3) to the nanomicrosphere aqueous solution loaded with the oxygen carrier is 1:1~1.5:1; the temperature of the constant temperature shaker is 30~40°C, the rotation speed is 100~250 r / min, and the coupling time is 30~60 min, the high molecular polymer in step (4) includes high molecular weight polymer A and high molecular weight polymer B, the high molecular weight polymer A includes one or more of methacrylic anhydride gelatin, poly (ethylene glycol) diacrylate or methacrylic anhydride chitosan, the high molecular weight polymer B includes one or more of oxidized dextran, oxidized hyaluronic acid, and oxidized sodium alginate; the mass percentage of high molecular weight polymer A is 5% to 25%, and the mass percentage of high molecular weight polymer B is 5% to 25%; the cross-linking agent is N, N-methylenebisacrylamide, and the photoinitiator is phenyl (2,4,6-trimethylbenzoyl) lithium phosphate; the free radical polymerization reaction is a blue light-induced free radical polymerization reaction, the blue light wavelength is 405nm, the power is 40~50w, the light initiation distance is 1~3cm, and the illumination time is 10~20s.

3. Use of the nanohybrid double network hydrogel based on the nanoenzyme complex according to claim 1 in the preparation of diabetic wound healing dressings.

Citation Information

Patent Citations

  • Multifunctional antibacterial dressing, preparation method and application

    CN113499473A

  • Bionic drug-loading nano-system combining cell membrane antagonism with nano-enzyme, preparation method and application

    CN113599368A